Principal Leadership Communication in Enhancing Teachers' Work Motivation - Yudha Pradhana; Audrey Danellea Rahmadhani; Muqoyla Fajrin; Niquita Chairunisa; Deasy Ayu Nandini (International Journal of Interdisciplinary Research, 2026)
In the field of education, principals play an important role in creating a conducive working environment for teachers. This study aims to analyze the leadership communication strategies employed by the principal in improving teachers’ work motivation at SMK Budi Asih Jakarta. This research used a qualitative descriptive approach with data collected through in-depth interviews with the principal as the main informant. The findings reveal that the principal applies interpersonal, situational, formal, and informal communication strategies to foster teachers’ work motivation. Family-oriented communication, coaching, emotional support, and task delegation adjusted to teachers’ conditions emerged as the primary approaches in creating a positive working environment. Guided by Situational Leadership Theory, the study identifies the implementation of directing, coaching, supporting, and delegating leadership dimensions in the principal’s communication practices. The novelty of this study lies in its exploration of leadership communication strategies within the context of a vocational school through the lens of situational leadership. The findings provide practical insights for educational leaders in developing adaptive communication strategies to enhance teachers’ motivation and strengthen a positive organizational climate in schools.